PENGARUH PERMAINAN SAINS TERHADAP KEMAMPUAN KLASIFIKASI DAN BERPIKIR KRITIS PADA ANAK USIA DINI - Baiq Wike Pratamaswari; Gunawan; Fahruddin (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of science games on the classification and critical thinking abilities of early childhood. The type of research used is a quasi-experimental design with a one-group pre-test post-test design. The research subjects included 15 children in group B at one of the schools in Pujut subdistrict, Central Lombok Regency. Data were collected through observation using observation sheets as research instruments, while data analysis was performed using Paired Sample t-test and Repeated Measures Repeated Measures MANOVA tests. The results showed that science games can improve children's classification and critical thinking skills. This was evident from the increase in the average scores between the pre-test and post-test results. Based on the Paired Sample t-test and Repeated Measures MANOVA tests, the significance values obtained were 0.000 for classification skills, 0.001 for critical thinking skills, and 0.000 for both simultaneously. All significance values were < 0.05, so the alternative hypothesis (Ha) was accepted. Thus, it can be concluded that science games have a significant effect on improving the classification and critical thinking in young children.